2014
DOI: 10.1016/j.intimp.2014.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Selective serotonin reuptake inhibitors as a novel class of immunosuppressants

Abstract: In the past decades, selective serotonin reuptake inhibitors (SSRIs) have been shown to exert several immunological effects, such as reduced lymphocyte proliferation, alteration of cytokine secretion and induction of apoptosis. Based on these effects, SSRIs were proposed as drugs for the treatment of autoimmune pathologies and graft-versus-host disease. This review summarizes preclinical and clinical evidence supporting a role for SSRIs in autoimmune diseases and graft-versus-host disease, and discusses what i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
63
0
8

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 76 publications
0
63
0
8
Order By: Relevance
“…The mechanisms underlying the effects of SSRIs on the immune system under normal and pathological situations remain to be clarified (Gobin et al, 2014). Taler et al (2008) and Gobin et al (2014) suggested that the immunomodulatory effect of SSRIs would be related to their pro-apoptotic activity, and to their action on lymphocyte proliferation and to cytokine secretion. This may have been the case in our work as a consequence of normalizing the altered neuroendocrine function in prenatally stressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms underlying the effects of SSRIs on the immune system under normal and pathological situations remain to be clarified (Gobin et al, 2014). Taler et al (2008) and Gobin et al (2014) suggested that the immunomodulatory effect of SSRIs would be related to their pro-apoptotic activity, and to their action on lymphocyte proliferation and to cytokine secretion. This may have been the case in our work as a consequence of normalizing the altered neuroendocrine function in prenatally stressed animals.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TNFα and IL-6 release, as well as promotion of IL-10 synthesis, are prominent among the antiinflammatory features of M2 macrophages [33,35,36] . Nevertheless, these antiinflammatory effects have been speculated to occur only at doses greater than the usual therapeutic range [37] , and SSRIs may rather be proinflammatory at lower doses, especially with prolonged use [38] . This is consistent with evidence from Kubera et al [27] , who found physiological levels of intracellular serotonin tend to promote TNFα and IL-6 synthesis in macrophages, whereas supraphysiological levels of extracellular serotonin were linked with downregulation of serotonin receptors serotonin receptors and with decreased release of with decreased release of proinflammatory cytokines.…”
Section: Ssri-associated Cardiometabolic Risk: Molecular Pathwaysmentioning
confidence: 99%
“…In the spleen, 5-HT increases monocyte differentiation into dendritic cells and early naive T-cell activation via the 5-HT 2A receptor [38,39]. Furthermore, it also has been shown that lymphocytic cytokine levels in mice are reduced after treatment with SSRI [40]. In a mouse model of viral hepatitis, the release of 5-HT by platelets was responsible for tissues damage caused by CD8 (+) T-cells, microcirculatory events, and reduced clearance of infiltrated viruses [33].…”
Section: Serotonin -A Chemical Messenger Between All Types Of Living mentioning
confidence: 99%